Sensitivity and specificity of the modified tandem walking test for vestibular hypofunction with chronic dizziness in young adults - Kılıç, Gamze; Şenocak, Emre; Aktürk, Adem; Çelikyurt, Cengiz (Journal of Surgery and Medicine, 2021)
Background/Aim: Patient comfort is greatly affected during videonystagmography (VNG), and more comfortable tests are needed for diagnosis. This study aims to evaluate the modified tandem walking test (MTWT) as an alternative pre-assessment method to the VNG test. Methods: A total of 3348 patients were recruited in this retrospective cohort study between 2015-2019 based on the inclusion criteria of having chronic dizziness (>3 months), being aged between 18-65 years, and having an interpretable VNG test result. All patients were examined by an otolaryngologist, and the examination phase consisted of three parts: Physical examination, VNG test, and performing MTWT. The sensitivity, specificity, and likelihood ratio of the MTWT were calculated with the relevant formulas. Results: The female/male ratio was 2.19, and there was no significant difference between the groups in terms of age (P=0.334). The number of patients who were VNG positive (regardless of MTWT), both VNG and MTWT positive, both VNG and MTWT negative, and VNG negative (regardless of MTWT) were 2519, 2000, 699, and 2519, respectively. The sensitivity and specificity of MTWT were 79.37%, and 84.31%, respectively. Conclusion: MTWT has good sensitivity and specificity, and we think that it can be a safe, simple, and accessible pre-diagnostic tool when VNG is not available or cannot be tolerated by the patients.